Association between ambient air pollution exposure and pregnancy outcomes in women treated with assisted reproductive technology: an updated systematic review and meta-analysis - Jian-Chao Qiao; Liang-Jie Sun; Pin-Peng Xie; Zhuo-Yan Li; Meng-Yue Zhang; Si-Yu Gui; Xin-Chen Wang; Jian-Kang Yang; Cheng-Yang Hu (BMC Public Health)
Abstract Background Ambient air pollution has been recognized as a potential threat to reproductive system function. However, studies investigating the relationship between air pollutants and pregnancy outcomes, particularly in the context of assisted reproductive technology (ART), has yielded inconsistent findings. Methods This study conducted an updated comprehensive search to identify observational studies published before October 14, 2023, that examined the associations between air pollution exposure and pregnancy outcomes among women undergoing ART. Meta-analysis using random effects models were employed to calculate pooled risk estimates of clinical pregnancy, biochemical pregnancy, and live birth. Results A total of 20 studies were included in the systematic review and meta-analysis, with 12 studies included in the quantitative synthesis. The results revealed that exposure to carbon monoxide (CO) (RR = 0.949, 95% CI: 0.900, 0.999; I2 = 73%) and nitrogen dioxide (NO2) (RR = 0.976, 95% CI: 0.961, 0.992; I2 = 10%) during the period from ovarian stimulation to oocyte retrieval was associated with lower clinical pregnancy rates. Similarly, exposure to CO (RR = 0.985, 95% CI: 0.975, 0.996; I2 = 0%) and NO2 (RR = 0.978, 95% CI: 0.961, 0.996; I2 = 27%) during this period reduced biochemical pregnancy rates. Conclusions Our study highlights the potential association between air quality and ART outcomes, underscoring the need for improvements in air quality to enhance reproductive success.